Health-related quality of life of patients undergoing haemodialysis therapy in Dar es Salaam, Tanzania - Msilanga, Daniel P; Punatar, Priyank; Ruggajo, Paschal (African Journal of Nephrology, 2023)
Background: Patients with kidney failure on maintenance haemodialysis therapy have a lower health-related quality of life (HRQOL) than matched controls without kidney failure. HRQOL is an important predictor of clinical outcomes among patients with kidney failure, yet there is a paucity of such data in Tanzania. We determined HRQOL among Tanzanian patients with kidney failure receiving maintenance haemodialysis therapy. Methods: A cross-sectional study was conducted at Muhimbili National Hospital (MNH) in Dar es Salaam, from June to October 2020. MNH is a tertiary public sector hospital with 50 dialysis machines. Here, the Kidney Disease Quality of Life Short Form-36 questionnaire was used to assess HRQOL in 209 patients (69% male; mean age 51.9 ± 13.5 years). Their scores were categorized as low if the overall mean was ≤50, and as high if the score was >50. Factors associated with lower HRQOL were identified using multivariate logistic regression. Results: Overall HRQOL was low (mean score 48.9 ±13.9) and the factors associated with the scores recorded were having less than three haemodialysis treatment sessions per week [adjusted odds ratio (OR) 1.356, 95% CI 0.707–2.254] and urea reduction ratio <65% (OR 2.229, 95% CI 1.238–3.014). Conclusions: The overall HRQOL of patients undergoing haemodialysis was low. Receiving less than three haemodialysis sessions per week and having a urea reduction ratio of less than 65% were associated with lower scores. These findings underscore the importance of providing adequate haemodialysis treatment in improving the quality of life of patients with kidney failure.